The use of impulse ventilation for smoke control in underground car parks - Viegas, J. (2010)
Impulse ventilation systems (IVS) are used to provide ventilation for covered car parks and to control the smoke in the event of fire. In this paper the interaction between the fire ceiling jet and the flow driven by jet fans is studied using CFD simulations. A sensitivity analysis considering important parameters as position and intensity of fire source, transversal distance between jet fans, restriction of exhaust flow rate and dimension of car park exhaust opening is carried out and rules for the design of 50 N thrust jet fans are deduced. An analytical model for the flow field near the ceiling is developed and compared with CFD simulations. This model is intended to support a first approach of the design of IVS. 2009 Elsevier Ltd. All rights reserved.